The political theology of Bruno Latour - Howles, T (2018)
Although references to religion permeate the work of Bruno Latour from beginning to end, these have generally been dismissed in the critical literature as being superficial and extraneous. And yet, Latour makes strong claims that an understanding of religion is integral to his philosophical system. In this study, I offer the first full critical engagement with Latour’s writing on religion and thus with Latour as a potential contributor to the discipline of theology. I argue that a critical engagement of this sort contributes to the development of a political theology. First, it provides a conceptual framework by which modes of political thought and behaviour that are prevalent within modernity can be critiqued theologically. Latour shows how modernity is continually deploying an epistemological appeal to transcendence and thus that it has the form of a covert religion or religiosity. This has the effect of de-politicizing the contemporary public realm. Second, it provides the means for a positive re-imagining or re-conceptualization of religion as that which stays within the realm of immanence, counteracting the de-politicizing effect of modernity and providing the basis for new forms of human connectivity, responsibility and agency at the present time. As a point of application, I propose that interaction with Latour’s writing will enable the discipline of theology to engage with questions surrounding the impact of the contemporary environmental crisis. Latour shows how existing modes of human political negotiation are proving inadequate to the task of addressing this challenge precisely because they are expressions of the de-politicizing ideology of modernity. What is needed is an affective, moral and spiritual transformation. I demonstrate how Latour’s political theology can make a vital contribution on this front, enabling the discipline of theology to be at the forefront of important debates about the future of global human society.